The role of immune- and lipid metabolism-related genes in macrophage polarization and prognosis of glioblastoma - Zhang, Yue; Xu, Xin; Li, Shuo; Liao, Chenlong; Yang, Xiaosheng; Zhang, Wenchuan (Frontiers in Oncology, 2025)
ObjectiveTo investigate the roles of immune- and lipid metabolism-related genes in macrophage polarization and their prognostic and therapeutic implications in glioblastoma (GBM).MethodsA total of 655 GBM samples from The Cancer Genome Atlas (TCGA) were stratified into immune and non-immune groups based on immune scores. Differentially expressed genes (DEGs) were identified, and their intersection with 859 lipid metabolism–related genes yielded 26 candidates. A 10-gene prognostic signature was constructed using univariate and least absolute shrinkage and selection operator (LASSO) Cox regression analyses and validated in both internal (TCGA) and independent (Chinese Glioma Genome Atlas, CGGA) cohorts. Functional enrichment, single-cell transcriptomic analysis, experimental validation, and drug sensitivity profiling were performed to assess the biological and therapeutic relevance of the identified genes.ResultsTen immune- and lipid metabolism–related genes were significantly associated with GBM prognosis. Key genes such as LGALS1, PLA2G5, and FABP5 were upregulated in high-risk patients and enriched in M2-like tumor-associated macrophages. Enrichment analyses indicated their involvement in immune regulation and lipid metabolic pathways. Their elevated expression in GBM tissues was confirmed by qRT-PCR and Western blot. Drug sensitivity analysis demonstrated a correlation between LGALS1 expression and the response to agents such as zoledronate and staurosporine.ConclusionsImmune- and lipid metabolism–related genes contribute to macrophage polarization and are closely linked to GBM prognosis. The identified gene signature provides prognostic value and potential therapeutic targets for immunometabolic modulation in GBM.